Determinant of Financial Distress in Conventional Rural Banks in Central Java: Before and during Covid-19 Period - Kushermanto, Andi; Rahayu, Titi; Kurnianingsih, Helen; Ulum, Akhmad Samsul; Fachrur, M. Maulidin; Alisa, Inayah Risqi (KnE Social Sciences, 2024)
Financial distress refers to a state in which a company is unable to generate sufficient income and has difficulty paying its debt, and this effect can threaten the company’s financial condition towards bankruptcy. This study aims to examine the influence of loan-to-deposit ratio, nonperforming loans, and return on assets on financial distress. Additionally, it conducts multigroup testing of these variables in the Covid-19 pandemic period. The population of this study is conventional rural banks in Central Java for the 2019–2020 period. The sample, consisting of 84 observations, was obtained using the purposive sampling method. The data analysis technique employed in this study is Partial Least Squares-Structural Equation Modeling (PLS-SEM), utilizing WarpPLS version 8.0 software. This study shows that loan-to-deposit ratio and nonperforming loans have a positive effect on financial distress, while return on assets has a negative effect on financial distress. Furthermore, the additional analysis shows that there are significant differences between the loan-to-deposit ratio and nonperforming loans on financial distress in the pre-Covid-19 period and during the Covid-19 period. However, there is no significant difference in the effect of return on assets on financial distress in these Covid-19 periods. Keywords: covid-19, financial distress, loan to deposit ratio, nonperforming loans, return on asset